Impact of Socio-Demographic and Economic Factors on Households’ Savings Behaviour: Empirical Evidence from Ethiopia - Vadde, Suresh (Indian Journal of Finance, 2015)
The main aim of the study was to investigate the determinants of households’ saving behavior in a microfinance institution (MFI). Taking 150 household respondents in the survey from the place of Wikro Town, Ethiopia, the paper attempted to analyze the savings behaviour of household clients of Dedebit Credit and Saving Institution (DECSI). The study used a structured questionnaire, in which potential households were questioned about their reactions to some specific situations. The results of the study revealed that among the socio-demographic factors, gender and number of dependents were found to be statistically significant ; while age, educational level, and marital status of the household heads were insignificant - that unlike most previous findings, they did not have any explanatory power on households’ saving behavior in the study area. With regards to economic factors, average monthly income, occupation, and home ownership were statistically significant, which implies that they had an explanatory power in determining the savings behavior of the households.